(untitled) (Journal of Surgical Sciences, 2019)
Crossed testicular ectopia (CTE) is an extremely rare anomaly in which deviation of testicular descent results in unilateral location of both testes. It usually presents as an inguinal hernia on the side of a fully descended testis and an impalpable testis with undeveloped hemiscrotum on the contralateral side. Most often the diagnosis of CTE is not made until surgical exploration. Few reports are available regarding CTE in infants or younger children. Though the patients of CTE usually present at a younger age, we report a case of crossed testicular ectopia in a 65-year-old male who was admitted in the department of surgery, Shaheed Suhrawardi Medical College Hospital (ShSMCH) with right sided inguinal hernia. Journal of Surgical Sciences (2015) Vol. 19 (1) : 39-41